A new species of Aphis Linnaeus (Hemiptera, Aphididae) living on Teucrium polium L. (Lamiaceae) - Barjadze, Shalva; Blackman, Roger L.; Ӧzdemir Işil (Zootaxa, 2015)
Aphis polii sp. n. living on Teucrium polium L. (Lamiaceae) is described, based on apterous and alate viviparous females and oviparous females. It has been collected from seventeen localities in mainland France, Corsica, Italy, Ukraine, Lebanon and Iran. The new species is similar to two other Aphis species that feed specifically on plants of the genus Teucrium, but has a relatively longer ultimate rostral segment. Characters are provided to discriminate between the three Teucrium-feeding species, and to distinguish the new species from other morphologically similar Aphis species that feed on Lamiaceae. Type specimens are deposited in the Muséum national d’Histoire naturelle, Paris, France (MNHN), the UMR Centre de Biologie pour la Gestion des Populations, Montpellier, France and the Natural History Museum, London, UK (BMNH).